2015
DOI: 10.1590/1982-0216201517611214
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento da linguagem e deficiência auditiva: revisão de literatura

Abstract: RESUMO: Este estudo tem como objetivo revisar as produções científicas acerca das relações entre desempenho da linguagem e deficiência auditiva, assim como analisar os estudos observacionais sobre a temática. Trata-se de revisão de literatura, no qual foram utilizados os descritores "Hearing Loss", "Child Language", "Perda Auditiva", "Linguagem", "Fonologia" e "Vocabulário" nas bases de dados do Portal Capes, Bireme, Scielo e Pubmed no período de julho a dezembro de 2012. Os critérios de inclusão foram artigos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
6
0
7
Order By: Relevance
“…It was observed that the characteristics of the children in the intervention groups certainly determined the needs for adaptations to be made (Lederberg, Schick, & Spencer, 2013), with emphasis on the time of sensory deprivation (Bornstein, 2018;Wake & Carew, 2016), the restricted use of hearing aids for some of them (Penna, Lemos, & Alves, 2015;Vasconcelos, & Pereira, 2015) and the late entry into the hearing (re)habilitation program (Bicas, Guijo, Delgado-Pinheiro, 2017;Oliveira, Penna, & Lemos, 2015;Tabaquim et al, 2013), which were factors verified in the sample and which should be considered in the development of strategies for phonological work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the characteristics of the children in the intervention groups certainly determined the needs for adaptations to be made (Lederberg, Schick, & Spencer, 2013), with emphasis on the time of sensory deprivation (Bornstein, 2018;Wake & Carew, 2016), the restricted use of hearing aids for some of them (Penna, Lemos, & Alves, 2015;Vasconcelos, & Pereira, 2015) and the late entry into the hearing (re)habilitation program (Bicas, Guijo, Delgado-Pinheiro, 2017;Oliveira, Penna, & Lemos, 2015;Tabaquim et al, 2013), which were factors verified in the sample and which should be considered in the development of strategies for phonological work.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 30 years, surprising technological and scientific advances have given children with hearing impairment access to speech sounds at a time favorable to their language development (Wake & Carew, 2016;Bornstein, 2018). Even so, due to the variables involved in the (re)habilitation process -such as: age at diagnosis, cause and degree of hearing impairment, time of use of hearing aid devices, family involvement in the therapeutic process (Bicas, Guijo, & Delgado-Pinheiro, 2017;Moret, 2017;Oliveira, Penna, & Lemos, 2015;Penna, Lemos, & Alves, 2015;Tabaquim et al, 2013;Vasconcelos & Pereira, 2015), among other factors -, hearing impaired children have a disadvantage in relation to hearing children in terms of phonological processing and are, therefore, a risk population for the acquisition of the ability to read (Goldberg & Lederberg, 2015;Lederberg, Schick, & Spencer, 2013;Naveka von Mentzer et al, 2013;Werfel, Douglas, & Ackal, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Quando as crianças apresentavam ausência de EOAT, eram realizadas Emissões Otoacústicas por Produto de Introdução A audição está diretamente relacionada ao desenvolvimento global da criança. Portanto, se houver alguma alteração auditiva as habilidades cognitivas, acadêmicas, sociais e de fala e linguagem serão afetadas 1 A incidência de perda auditiva em crianças com IRDA pode chegar a 8,3% 4 . Podendo se manifestar ao nascimento ou de forma tardia, nos primeiros meses de vida 5 .…”
Section: Métodounclassified
“…Desta forma, em conjunto com os dispositivos eletrônicos, enfatiza-se a importância da terapia fonoaudiológica, com ênfase na função auditiva para o desenvolvimento da linguagem oral, com profissionais competentes e especializados, em parceria com a família (Melo & Lara, 2012). O amadurecimento das habilidades auditivas levará à criança ao aprendizado e desenvolvimento da linguagem receptiva e expressiva, oral e escrita, além da compreensão e atribuição de significado (Oliveira, Penna, & Lemos, 2015). Além disso, para…”
Section: Frequência Do Uso Horas De Uso Indivíduosunclassified